Normal viability of Kai1/Cd82 deficient mice. Issue 8 (8th February 2013) - Risinger, John I.; Custer, Mary; Feigenbaum, Lionel; Simpson, R. Mark; Hoover, Shelley B.; Webster, Joshua D.; Chandramouli, Gadisetti V. R.; Tessarollo, Lino; Barrett, J. Carl
Abstract The KAI1/CD82 tetraspanin is a widely expressed cell surface molecule thought to organize diverse cellular signaling processes. KAI1/CD82 suppresses metastasis but not tumorigenicity, establishing it as one of a class of metastasis suppressor genes. In order to further assess its functions, we have characterized the phenotypic properties of Kai1/Cd82 deleted mice, including viability, fertility, lymphocyte composition, blood chemistry and tissue histopathology, and of their wild‐type and heterozygote littermates. Interestingly, Kai1/Cd82−/− showed no obvious genotype associated defects in any of these processes and displayed no genotype associated histopathologic abnormalities after 12 or 18 months of life. Expression profiles of non‐immortal, wild‐type and Kai1/Cd82−/− mouse embryo fibroblast (MEFs) indicated distinct sex‐specific and genotype‐specific profiles. These data identify 191 and 1, 271 differentially expressed transcripts (by twofold at P < 0.01) based on Kai1/CD82 genotype status in female and male MEFs, respectively. Differentially expressed genes in male MEFs were surprisingly enriched for cell division related processes, suggesting that Kai1/Cd82 may functionally affect these processes. This suggests that Kai/Cd82 has an unappreciated role in the early establishment of proliferation and division when challenged with a new environment that might play a role in adaptability to new metastatic sites. © 2013 Wiley Periodicals, Inc.